Surgical management of severe osteoradionecrosis of the mandibular bone by using double free flap reconstruction. Issue 1 (January 2018) - Rommel, Niklas; Kesting, Marco Rainer; Rohleder, Nils Hagen; Wolff, Klaus-Dietrich; Weitz, Jochen
Abstract: Purpose: Osteoradionecrosis (ORN) of the jaws represents one of the most severe complications after primary or adjuvant radiation therapy (RT) of large head and neck tumors. In advanced ORN cases, surgical management is generally considered the therapy of choice. However, in several severe ORN patients with extensive bone and soft tissue defects, functional and aesthetic reconstruction represents a huge challenge for any surgeon, with an increased risk of post-operative wound healing disorders. Our aim here was to perform a double free flap technique as a therapeutic option in this difficult patient collective and to evaluate the post-operative outcome. Materials and methods: 15 patients with advanced and severe ORN undergoing mandibular and soft tissue reconstruction with a double free flap were retrospectively reviewed. In one single operation involving a three-team approach, an obligatory free fibular flap (FFF) was freely combined with another free flap according to the desired features: anterolateral thigh (ALT) or vastus lateralis flap (VLF), radial forearm flap (RFF) and latissimus dorsi flap (LDF). Results: We found sufficient wound healing in the head and neck region in all patients with no need for any additional surgical intervention. The overall flap success rate was 93.3%, although three revisions of anastomosis were necessary. Furthermore, prolonged stay on the intensive care unit (ICU) and extended hospitalisation were avoided. Conclusion: The double free flap technique with an obligatory FFF provides a suitable surgical solution for the treatment of patients with severe ORN of the mandibular bone for which other conservative or surgical therapy strategies have reached their limits.